Case Report of Warfarin Induced upper gastrointestinal bleeding - Kavya Vinod Mankulangara, Aswani Sreekumar, Priya Vijayakumar (Journal of Applied Pharmaceutical Science, 2017)
Warfarin is an oral vitamin k antagonist prescribed to those patients for the treatment and prevention of venous thromboembolism. The major challenges to be faced during the therapy were a greater risk for both major as well as minor bleeding, which makes the regular monitoring of INR (international normalized ratio) mandatory. Here we report a case study of 80 year old male who presented to casualty with the complaints of vomiting fresh blood in large quantities due to consumption of warfarin three times in a day for past 2 weeks. Patient was on anticoagulation therapy for paroxysmal atrial fibrillation since 2012 and was taking all his medications alone, he was independent in activities of daily living and instrumental activities of daily living. The blood investigation revealed anemia (Hemoglobin:6.1g/dl).He was immediately transfused with packed RBC and fresh frozen plasma to replenish the body reserves. Prothrombin time (PT)/INR was reported undetectable and warfarin was withheld from the past medications and was restarted at INR 1.56.The overdose has led to additional monitoring and prolonged hospital stay. Furthermore this case highlights the need for a better communication by providing counselling regarding all aspects of medications as well as lifestyle modifications and also by giving patient information leaflets.
Keywords: Warfarin, INR, Atrial fibrillation, Gastro Intestinal(GI) bleeding.